Rancang Bangun Aplikasi Perpustakaan pada Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Surabaya - Rahardhi, Ignatius; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Surabaya is an educational institution that has supporting facilities, one of them is the library. There are some problems in the LP3I’s Library, such as: the collection is less well documented, there is no reminder to remind the borrowers whose term loan collection will be expired, and there are no reports like visitor reports and collection report that often borrowed, so the librarians understand which collections is often borrowed, and who visit the library frequently.From the problems, offered solution is a library application that uses SMS Gateway to provide a reminder for members that loan collection period has expired. The study also applies the waterfall method. The method sequentially starting from requirements analysis, system design, programming, testing programs, implementation and then maintenance program.The results showed that the application of web-based library can help officers in circulating collection and reporting. In addition, library members can also be helped with the search collections and a reminder to return the library collection. Keywords: Library, Circulation, SMS Gateway.